MENUJU HUKUM PERKAWINAN ISLAM PROGRESIF TOWARDS PROGRESSIVE ISLAMIC MARRIAGE LAW - Wahyudi, Muhamad Isna (Jurnal Hukum dan Peradilan, 2014)
There are some provisions on the Bill of Religious Judicature Substantial Law on Marriage that need to be formulated in accordance with the present time. In this way, the Islamic Law of Marriage in Indonesia will be progressive and not discriminative against women. Those provisions include the pillar of marriage, the age of marriage, the guardian of marriage, and the status of child. This article tries to contextualize those provisions in accordance with the present time using hermeneutical approach. As the result, the registration of marriage should be one of the pillars of marriage, the age of marriage should be formulated by considering women’s reproduction health, the guardian of marriage for the bride is not pillar of marriage, and the child of pregnant woman marriage is counted as legal child whose lineage to both parents. Keywords: pillar of marriage, the age of marriage, the guardian of marriage, and the status of child.